2017
DOI: 10.4081/ripppo.2017.273
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatments are as effective as pharmacotherapies in the treatment of adult depression: a summary from Randomized Clinical Trials and neuroscience evidence

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 57 publications
(66 reference statements)
2
14
0
Order By: Relevance
“…The effects of psychological interventions for treatment of adult depression have been shown to be comparable to those achieved with pharmacological intervention, and are probably longer-lasting (Cuijpers and Gentili, 2017). In particular, cognitive-behavioural therapy (CBT) is a common and effective psychological intervention for the treatment of depression (Churchill et al ., 2002; Butler et al ., 2006; National Institute for Clinical Excellence, 2009; Shafran et al ., 2009; Lepping et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of psychological interventions for treatment of adult depression have been shown to be comparable to those achieved with pharmacological intervention, and are probably longer-lasting (Cuijpers and Gentili, 2017). In particular, cognitive-behavioural therapy (CBT) is a common and effective psychological intervention for the treatment of depression (Churchill et al ., 2002; Butler et al ., 2006; National Institute for Clinical Excellence, 2009; Shafran et al ., 2009; Lepping et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…many patients remain resistant to treatment 5,6 . In response, current advances in neuroscience have identified additional mechanisms of the disorder's underlying pathophysiology, leading to alternative or additional pathogenic hypotheses and therapeutic interventions 5,7 .…”
mentioning
confidence: 99%
“…Several evidence-based treatments are available for adults with depression. Meta-analyses and reviews have shown that different treatments are effective (e.g., [ 3 , 4 ]). Cognitive Behavioral Therapy (CBT) has been researched the most.…”
Section: Introductionmentioning
confidence: 99%